Agressividade e o adolescente em conflito com a lei: um estudo psicanalítico - CRUZ, Alexandre Théo de Almeida (2007)
This masters degree course conclusion work is a theoretical research based on the psychoanalysis and the fundamental psychopathology, and it presents a study on aggressiveness and the adolescent in conflict with the law. First of all, it is shown how the aggressiveness is part of the subjectivity, that is, it exists inside all the human beings, according to the analysis made by Freud in his book Civilization and its Discontents (1930); after that, the aggressiveness is studied on Winnicott (2002), who also affirms that this [the aggressiveness] is part of the subjectivity and emphasizes the importance of understanding this concept with its relationship with the antisocial tendency and the delinquency. Then, a reflection is brought up about the antisocial behavior and the delinquency, where the thought of Vilhena (2002) is underlined. This author differentiates aggressiveness and violence and at the same time, articulates the concepts of emotional privation with contemporary aspects; showing that the family is the support of those adolescents in conflict with the law, but as well, the failure of the parents regarding their children, which is a fact that should be taken into account in the study of the aggressiveness, the antisocial tendency and the delinquency. Finally, Marta Gerez-Ambertín's theory (2004) is presented on the "subject of the action". In this authors opinion, the subject should have a subjective compromise with his actions and speech. Working hypothetically, its said that the adolescents in conflict with the law try to find answers to their conflicts and unconscious desires. Yet, to the adolescent in conflict with the law, it is necessarily offered the possibility to talk about his action and assume the responsibilities for his behavior.